Inventarisasi Tanaman Berpotensi Alelopati - Pasaribu, Putri Apriani; Armiati, Rika; Nurandi, Amelia Putri; Tanjung, Indayana Febriani; Hasibuan, Febry Ramadhani (MODELING: Jurnal Program Studi PGMI, 2023)
Investarization of potential allelopathy plants, allelopathy substances are compounds released by plants into the environment where other plants grow. This study aims to find out the conditions of the allelopathic plant research area in the North Sumatra State Islamic University area and find out the types of weeds found in the North Sumatra State Islamic University area. Based on the research conducted in the observation, it was found that there were 3 species of sea cypress plants and 3 species of pine plants.